Virtual aggressions and ciberbullying: Gender violence in social networks, the experience of youth and teenagers - Esteban Ramiro, Beatriz; Gómez Medrano, Mónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The results of a research on young population positions around cyber-aggressions and gender violence on social media. The sample consisted of 317 people between 15 and 19 years old. The Gender Violence Questionnaire 2.0 (Donoso et al., 2014) is used as the main technique. The results show direct experiences of harassment. Girls also have a high perception of risk in virtual contexts: they see sexist and violent behaviours towards women in social networks, Abstract in English. 100 words maximum.